Development of Video-Based on Contextual Teaching and Learning Electric Energy Subtheme - Fariq Isy Ely Rusly; Rifqi Aulia Erlangga (Prodi PGMI IAIN Salatiga, 2020)
This study aims to develop and know the implementation of the Contextual Teaching and Learning (CTL) video about Electrical Energy Materials for Class VI Students of Islamic Elementary School. The method used in this study was Research and Development with ADDIE steps. The ADDIE is a model consisting of five steps that are Analyze, Design, Development, Implementation, and Evaluation. The study concludes that: 1) Analyze everything needed in development, 2) Design of CTL video framework in both layout and appearance, 3) Development of CTL video teaching materials from the collection of materials, preparation, validation, revision, and production of CTL videos, 4) Implementation CTL videos in learning, 5) Evaluation of the CTL video used concerning its effectiveness, practicality, and attractiveness in learning. Subjects in this research were 30 student Islamic Elementary School of Siti Sulaechah Semarang, Central Java. The data collection techniques used are interviews and questionnaires. The data analysis method in this research is qualitative and quantitative data analysis. SPSS 16 is used for quantitative analysis. The results showed as follows, 1) teachers need learning videos that are innovative, interesting, and can improve students environmental care attitudes; 2) the form of development in the form of CTL videos through the steps of analysis, design, development, application, and evaluation; and 3) Contextual Teaching and Learning-based Learning Videos can in increasing environmental attitudes (paired-sample t-test, α = 0.00 0.05).